The Use of Tanjungpura University’s e-Learning-Moodle LMS during Online Learning: Problems, Solutions and Continuation - Suparjan Suparjan; Nining Ismiyani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to investigate the problems, solutions, and opinions about the use of the Tanjungpura University’s e-learning-Moodle LMS as learning media during the covid-19 pandemic by students of the Elementary School Teacher Education Study Program at the Faculty of Teacher Training and Education of Tanjungpura University in Pontianak, West Kalimantan. Respondents in this study were selected based on the characteristics of gender, and semester classifications. The qualitative research approach was employed in this study, utilizing semi-structured interviews where the interview questions underwent a piloting phase. The results of the study showed that the challenges faced by the students in using Moodle LMS included network instability, application errors, application disadvantages and the level of technology literacy which were followed up by shortcut tricks and strategies the respondents came up with to overcome them. In general, respondents gave a positive response to the use of Moodle LMS which can be seen from their preference for Moodle LMS over other LMS’s, claim of its suitability for use in learning, and willingness to recommend it to other potential users. However, all respondents revealed that they prefer face-to-face learning to online learning.